THE EFFECT OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND COUNTERPRODUCTIVE BEHAVIOR ON EMPLOYEE PERFORMANCE WITH EMPLOYEE ENGAGEMENT AS AN INTERVENING VARIABLE IN BPR - Agustinus Setyawan; Agnes Triyanti (Management Department, Faculty of Economics and Business, Universitas Jambi, 2020)
Banking is the one that provides services to customers, in order to create a good image of a businessman. This research aims to analyse the impact of organizational citizenship behavior, counterproductive work behavior, with employee engagement as variable intervening through the impact of employee performance in Bank Perkreditan Rakyat in Batam. The difference in behaviour of each employee is a determinant of their performance in the company. Increased the competition in the banking sector, which continues to compete to create better services. The behaviour of employee has positive and negative that can affected by colleagues around them. Positive behaviour will affect good performance for the organization and negative behaviour will become an obstacle to an organization. Based on the relationship of existing problems, this research needs to determine the effect of employee behaviour can be involved in their own performance. Based on authors survey that people who works on Bank Perkreditan Rakyat shows employee behavior that needs to be considered in employee performance appraisal. By looking at several factors and the impact to these employees on the company. In general, the services provided to the financial services sector are important aspects of the banking sector to improve the quality of the organization.